Effects of red wine on cardiovascular diseases - Ramian, Jan; Bator, Piotr; Razik, Michał; Rozwadowska, Patrycja; Rybak, Jakub; Magiera, Barbara; Magiera, Karol; Razik, Wiktor (Journal of Education, Health and Sport, 2024)
Introduction and purpose: The purpose of this scientific paper is to review the current knowledge of the effects of red wine on human health, particularly with regard to cardiovascular disease. State of Knowledge: Since the 1990s, red wine has gained its status as a health-promoting alcohol through the French Paradox - when drunk in moderate amounts, it protects against cardiovascular disease. The authors have collected scientific papers on the health effects of alcohol, red wine and resveratrol-a polyphenol that is the main component with health-promoting effects of wine. On their basis, they analyzed the assumptions of the positive effects of wine reaching inconclusive conclusions. Summary: Despite the fact that both ethanol and resveratrol have a positive effect in in vitro studies, in population studies their effect is much less significant, either because the negative behavioral-health effects in the case of ethanol are omitted or the actual effective doses of resveratrol are omitted.